NEW INITIATOR SYSTEMS FOR POLYMERIZATION OF VINYL MONOMERS TERTIARY HYDROPEROXIDES — COMPLEX OF COPPER(II) CHLORIDE WITH PIPERIDIN-1-YL PIPERIDINE-1-CARBODITHIOATE - A. V. Grekova; P. A. Ivanchenko; I. I. Seifullina; G. N. Khitrich (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2015)
Kinetics of polymerization of styrene in-bulk initiated by tertiary hydroperoxides of butyl and cumene, by the complex of copper(II) chloride with piperidin-1-yl piperidine-1-carbodithioate and systems on their basis in a temperature range 293—363 K is studied. The kinetic parameters of polymerization process are determined. It is set that application of the double-base systems tertiary hydroperoxides — complex of copper(II) chloride with piperidin-1-yl piperidine-1-carbodithioate for polymerization of styrene is accompanied by the substantial decline of energy of activation of initiating.